THE ROLE OF MOTIVATIONAL LANGUAGE AS A MODERATION BETWEEN VARIOUS BEHAVIOR KNOWLEDGE OF WORK BEHAVIOR INNOVATIVE AND JOB SATISFACTION - Yuliza, Mai; Azliyanti, Elfitra; Siswadhi, Ferry (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2024)
The purpose of this study was to explore the extent to which the influence of knowledge sharing behavior on innovative work behavior and employee job satisfaction with motivational language as a moderating variable. Hypothesis testing was tested using STATA analysis. The tests used include validity analysis, reliability analysis and regression hypothesis testing. Data collection was carried out by distributing questionnaires to 45 employees at PT Serumpun Indah Perkasa. The results of the study found that knowledge-sharing behavior has a positive effect on innovative work behavior, while knowledge-sharing behavior has a negative effect on employee job satisfaction. Furthermore, motivational language is a moderating variable of the relationship between knowledge sharing behavior and innovative work behavior.